Between Leisure and Pressure—Veterinarians’ Attitudes towards the Care of Competition Horses in Germany, Austria and Switzerland - Svenja Springer; Denise Isabell Mihatsch; Herwig Grimm; Florien Jenner (Animals, 2023)
Equine veterinarians face a range of challenges when attending competition horses. Athletic goals may significantly impact veterinary decision making, and the veterinarian’s work can be complicated by reputational considerations and rival opinions during an assessment of whether a horse is “fit to compete”. Using an online questionnaire, we found that the majority of German, Austrian and Swiss equine veterinarians (N = 172) surveyed agreed that the owners of competition horses are more likely than owners of leisure horses to approach them with clear treatment ideas, and that the former have higher expectations of the medical services provided. The data also show that the veterinarian’s reputation plays a more important role in the competition sphere. Using a case vignette, we established that, on the grounds of equine welfare, the majority of respondents indicated that they would decide against starting a dressage horse with low-grade lameness in a competition. Those respondents who indicated that they would approve a start of the dressage horse indicated that a horse with a low-grade lameness was fit enough “to compete”. We conclude that clearer definitions of phrases, such as “fit to compete”, may be helpful in guiding veterinarians as they discharge their professional responsibilities during competitions and reduce the reputational stress they experience in this working context.